Comparative Analysis of Financial Reporting under PSAK 73 and PSAK 30: Implications for Lease Accounting Practices - Wiyarti, Evy Steelyana; Fadlurahman, Muhammad Harris (Universitas PGRI Madiun, 2024)
The purpose of this study was to determine the differences in the presentation of financial statements in the implementation of PSAK 30 and PSAK 73 and to analyze the company's performance after the implementation of PSAK 73. The method used in this study was a qualitative method with descriptive analysis. In this study, interviews and data collection were conducted. The data and information obtained are processed by comparison and ratio calculation. The results of the study are the differences between the implementation of PSAK 30 and PSAK 73 at PT. KBS can be directly seen in the increase in total assets, total liabilities and total equity. In the calculation of the ratio, several results show an increase in value after the application of PSAK 73. It is concluded that since the application of PSAK 73, the company's performance has increased and financial reporting has become more efficient and transparent.